Oral literature in Africa - Finnegan, Ruth H. (World oral literature series, 2012)
"This revised edition makes Finnegan's ground-breaking research available to the next generation of scholars. It includes a new introduction, additional images, and an updated bibliography, as well as original chapters on poetry, prose, 'drum language' and drama, and an overview of the social, linguistic and historical background of oral literature in Africa."--Back cover